MODEL KEPEMIMPINAN TRANSFORMATIF (KAJIAN KEPEMIMPINAN TRANSFORMATIF DI LEMBAGA PENDIDIKAN ISLAM) - M. Yusuf Aminuddin (Al Hikmah: Jurnal Studi Keislaman, 2017)
Transformative leadership is a leadership model which gives direction of positive changes in organizations or Islamic educational institutions. Based on the author's observation, transfomative leadership is not only oriented on the effort in creating changes and improving the quality of members' resources, but also as efforts in order to improve the quality which is more responsive and dynamic with the development of period. Based on the previous experts' opinion, none had ever stated that transformative leadershio should be sensitive toward the development of period and see to the values taught by Prophet Muhammad. Historically, transformativr leadership was established among the leaders of islamic boarding house, it was if that leadership is translated as an effort of making changes and being sensitive toward the organization's interest. Transformative leadership which can affect islamic educational institution will give good impacts in order to develop the organization's productivity, in which their Islamic vision and mission will be achieved effectively. This is because transformative leaders can become a figure and inspiring leader of those organizations, in which they can grow the members' loyalty, also be able to solve old problems with new methods.